Postural control during a transition task in haemophilic children, adolescents and young adults with haemophilic ankle arthropathy. Issue 4 (19th April 2018) - Deschamps, K.; Staes, F.; Eerdekens, M.; Peerlinck, K.; Hermans, C.; Vandesande, J.; Lobet, S.
Abstract : Background: The aim of this study was to determine whether young haemophilic boys with and without MRI‐based signs of ankle arthropathy demonstrate reduced balance ability during a transition task with eyes open and eyes closed. Methods: Thirty‐four haemophilic bodies and 28 typically developing boys aged 6‐20 years participated to this study. Structural integrity of the tarsal foot joints of all haemophilic boys was assessed with MRI. All participants performed a standard transition task from double‐leg stance to single‐leg stance with eyes open and eyes closed. Comparison of balance features derived from the centre of pressure displacement captured by a single force platform was performed between the different haemophilia subgroups and sex‐age‐height matched peers. Findings: The haemophilic boys without signs of arthropathy presented only a higher intermediate phase velocity during the eyes closed condition ( P  = .05). The haemophilic boys with signs of arthropathy had significantly higher displacement after the time to new stability point, and 95% Ellipse Sway Area and Balance Area compared to their matched peers during eyes open test ( P  < .05). Similar findings were observed during the eyes closed test for the displacement after the time to new stability point and 95% Ellipse Sway Area ( P  < .05). No significant differences were observed between affected and non‐affected side of the unilateral affected patients. Interpretation: We suggest that the pathophysiological cascade associated with chronic bleeding episodes should not be considered as a "simple" musculoskeletal injury, hence more as a complex neurophysiological dysfunction which may originate both from unilateral and bilateral deterioration of the musculoskeletal system.